Rabbinic traditions between Palestine and Babylonia - Nikolsky, Ronit.; Ilan, Ṭal. (Ancient Judaism and Early Christianity, 2014)
In this book various authors explore how rabbinic traditions that were formulated in the Land of Israel migrated to Jewish study houses in Babylonia. The authors demonstrate how the new location and the unique literary character of the Babylonian Talmud combine to create new and surprising texts out of the old ones. Some authors concentrate on inner rabbinic social structures that influence the changes the traditions underwent. Others show the influence of the host culture on the metamorphosis of the traditions. The result is a complex study of cultural processes, as shaped by a unique historical moment.